Phylogenetic Analysis of Cyclocheilichthys apogon and Cyclocheilichthys armatus (Fish: Cyprinidae) from West Sumatra - Dewi Imelda Roesma; Djong Hon Tjong; Syaifullah; Dyta Rabbani Aidil (Bogor Agricultural University, Indonesia, 2023)
Cyclocheilichthys apogon (Beardless Barb fish) and Cyclocheilichthys armatus (Hihgfin Barb fish) in West Sumatra is known by the local name Turiak and Catua fish, respectively, are economically important species. Reducing populations and limited biological information about these fishes make their genetic diversity and phylogenetic relationships crucial. The genetic variation was investigated by analyzing the sequencing of a part of mitochondrial DNA Cytochrome b (Cyt b) and Cytochrome oxidase-I (COI) genes of 23 individuals collected from West Sumatra populations. Phylogenetic analysis revealed the monophyletic lineage of the Cyclocheilichthys group and supported Anematichthys as the synonym of Cyclocheilichthys. C. armatus was closely related to C. janthochir and separated from C. apogon with sequences divergence were 12.7-14.0% (Cyt b) and 9.4%-10.0% (COI). C. apogon and C. armatus have low haplotype diversity and genetic diversity, respectively. Genetic diversity within and among populations with sequences divergence was 0.0-0.8% (Cyt b) and 0.0%-0.7% (COI), respectively. The low-level diversity may signify a possibility of gene flow within and among populations. The current data suggests all populations as a single stock unit. Present genetic information is important to establishing effective population management, conservation, and breeding strategies for Turiak and Catua fish.